Investigation on Viscoelastic Poisson’s Ratio of Composite Materials considering the Effects of Dewetting - Huiru Cui; Weili Ma; Xuan Lv; Changyuan Li; Yimin Ding (International Journal of Aerospace Engineering)
A direct numerical method is introduced herein to investigate time-dependent Poisson’s ratio of solid propellant based on a representative volume element (RVE) model. Time-dependent longitudinal and transverse strains are considered in the calculation of time-dependent Poisson’s ratio under the relaxation test. The molecular dynamics (MD) packing algorithm is used to generate the high area fraction RVE model of solid propellants consisting of ammonium perchlorate (AP) particles whose radius follows lognormal distribution. In order to simulate the dewetting response of the interface between particles and matrix, the PPR model is modified and utilized during the analysis. Time-dependent Poisson’s ratio is measured under different cohesive parameters, loading conditions (loading temperature, loading rate, and fixed strain), and area fraction. Numerical results reveal that time-dependent Poisson’s ratio can be nonmonotonic or monotonic according to the different cohesive parameters. A concept of critical cohesive parameters is proposed to judge whether the monotonic property of time-dependent Poisson’s ratio appears or not. According to the numerical analysis, the cohesive contact and the shrinkage of the bulk element are two main factors which will control the change of monotonic property. All time-dependent Poisson’s ratios will increase at the beginning of the relaxation stage because the effects of cohesive contact can be ignored compared with the large shrinkage of the bulk element. However, with the increased shrinkage of the bulk element, the increased cohesive contact will defend further shrinkage at the same time. Although the shrink of the bulk element never changes its direction, the ratio of the transverse strain to longitudinal strain may decrease or keep increasing in this stage. When transverse and longitudinal strains stop to change, all time-dependent Poisson’s ratios will achieve their equilibrium values.